Preparation of 4A-zeolite-based Ag nanoparticle composite catalyst and research of the catalytic properties. Issue 4 (10th December 2014) - Hu, Xiaosong; Bai, Jie; Wang, Junzhong; Li, Chunping; Xu, Wei
Abstract : 4A-zeolite base silver nanoparticles (Ag NPs) composite catalyst was prepared and the catalytic properties were researched. Abstract : A 4A-zeolite-based silver nanoparticle (Ag NPs) composite catalyst was prepared and its catalytic properties were studied. A hydrothermal method was used to synthesis 4A-zeolite from coal gangue raw material. Ag NPs were prepared by an in situ reduction method. The 4A-zeolite-based Ag NP composite catalyst was prepared by impregnation method. The catalyst was analyzed by a series of characterization techniques, such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV-visible spectroscopy (UV-vis), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), etc. The characterization results indicated that the Ag NPs were uniformly distributed on the 4A-zeolite. The catalyst was then used to catalyze the epoxidation of styrene. The oxidant was tert -butyl hydroperoxide (TBHP), and isopropanol was used as the solvent. This demonstrated the excellent catalytic properties of the composite catalyst. The results showed very high conversion of styrene (72.1%) and excellent styrene oxide (SO) selectivity (59.5%). In addition, the joint selectivity of SO and benzaldehyde (BZ) reached 93.3%.